أفعال الكلام في عبرية العهد القديم: النظرية البراجماتية: دراسة دلالية سياقية - علي، هاجر مصطفى إبراهيم Ali, Hajar Mustafa Ibrahim (جامعة قناة السويس - كلية الآداب والعلوم الإنسانية, 2019)
يدرس هذا البحث واحدة من نظريات البراجماتية اللسانية في علم اللغة الحديث؛ ويطبقها على أحد مستويات العبرية القديمة (عبرية العهد القديم)، من خلال المنهج الوصفي، وينقسم البحث إلى جزئيين: جزء يعرض ظاهرة أفعال الكلام ومصطلحاتها الأساسية ونشائها وأقسامها ومفاهيمها، والجزء الآخر تطبيق للنظرية على عبرية العهد القديم. وتنتمي ظاهرة "أفعال الكلام إلى البراجماتية في حين يدرجها البعض تحت البحث الدلالي؛ ويعرف "الفعل الكلامي" بأنه أصغر وحدة اتصالية في اللغة؛ وهو عبارة عن جملة أو عبارة تحتوي على فعل أدائي أو تتضمن معناه، وفي حين النطق بتلك الجملة أو العبارة فإنها "لا تنشئ قولا فحسب بل تنجز فعلا في الوقت نفسه"، أو تحفز على القيام به.
This research studies one of the theories of linguistic pragmatism in modem linguistics, and applies it to one of the levels of ancient Hebrew (Old Testament Hebrew), through the descriptive method. The research is divided into two parts: one part presents the phenomenon of speech acts, their basic terminology, their origins, divisions and their concepts, and the other part presents an application of the theory to the Hebrew of the Old Testament. speech acts belongs to pragmatism, while some include it into semantic research; "speech act" is defined as "the smallest communicative unit in language, and it is a sentence or phrase that contains a "per formative verb" or includes its meaning, and while pronouncing that sentence or phrase, it "don't just create a saying, but performs an action at the same time", or stimulates action with it.
Keywords: علم اللغة البراجماتي -- البراجماتية -- اللسانيات -- اللغة العبرية -- أفعال الكلام